(untitled) (Transport systems and technologies, 2021)
The market of bunkering services forms one of the most important segments of world trade in oil products. In fact, the bunker market provides the work of the entire shipping industry, the share of which in world GDP is growing steadily, and by 2018 was estimated at 10 to 20%. Currently, fuel bunkering is a problem for Ukrainian seaports. Over 15 years, the annual volume of bunkering in Ukrainian ports has decreased tenfold. In Ukraine there are necessary coastal bases in Kherson, Nikolaev, other places. Bunker companies can easily find the right number of bunkers on the market for service in our ports. The volume of the world bunker market is characterized by huge and constantly growing needs of the world navy in material and technical supply of fuel of the vessels of the most different function in scales of the World ocean. The determining factor of regional demand for bunkering is the intensity of vessel traffic. Demand volumes depend primarily on the number of calls to local ports, the scale of port activity, tonnage turnover, the geography of sea routes in the region, the proximity of busy shipping routes and the service of transit flows. In addition, the availability of infrastructure (technical, organizational, information) and adjacent sources of competitive fuel supply at the prices of local refineries (refineries), as well as a range of services, quality of service, traditional procurement, customer confidence. The largest bunker centers in terms of bunker fuel sales per year are Singapore, Fujairah, Rotterdam, Hong Kong, Busan, Piraeus, Antwerp, Kaohsiung, Suez Canal, Panama Canal, Houston and Gibraltar. When organizing the flight according to two schemes, two ports for bunkering were considered: Istanbul and the Pivdenny. As a result of calculations in two directions, it can be concluded that Ukrainian ports are attractive for bunkering ships in technological and economic terms. Therefore, when changing the design scheme of the bunker in the ports of Ukraine, you can get some benefits. Both carriers and bunker companies may be interested in this.